Answer:
f = 3
g = -1
h = 6
r = 18
Explanation:
Box 1
f(x) =
-
+
+4x+15 with x = 3
f(3) =
-
+
+ 4(3) + 15
Reorder
Evaluate
Multiply
3f = 2 x 81 - 12 + 27 +16 x 9 + 12 +15
3f = 162 - 324 + 144 + 12 + 15
3f = 9
3 ÷ 3
f = 3
Box 1
g(x) =
-
- 7x - 36 with x = 6
g(6) =
-
- 7(6) - 36
g6 = 3 x 216 - 576 - 42 - 36
g6 = -6
6 ÷ 6
g = -1
Box 2
h(x) =
-
- 3 with x = -1
h(-1) =
-
-3
h-1 = -5 + 2 -3
h-1 = -6
-1 ÷ - 1
h = -6
Box 2
r(x) =
-
+ 5x - 2 with x = 2
r(2) =
-
+ 5(2) - 2
r2 = 64 - 36 + 10 - 2
r2 = 36
2 ÷ 2
r = 18